Climate and forest attributes influence above‐ground biomass of deciduous broadleaf forests in China. (8th December 2022) - Chen, Guoping; Cai, Qiong; Ma, Suhui; Feng, Yuhao; Fang, Wenjing; Ji, Chengjun; Zhu, Jiangling; Wang, Zhiheng; Wang, Shaopeng; Tang, Zhiyao; Fang, Jingyun
Abstract: Forests provide a huge carbon pool, a substantial portion of which is stored in above‐ground biomass (AGB). Deciduous broadleaf forests in China are an essential component of global deciduous broadleaf forests, yet the impacts of climate and forest attributes on their AGB are not well understood. Using a comprehensive forest inventory database from 772 plots distributed across temperate and subtropical deciduous broadleaf forests in China (23.51°–42.53°N and 104.24°–128.27°E), we applied variance partitioning analysis, model selection analysis and structural equation models to explore how climate and forest attributes (species diversity, community‐level functional traits and stand structures) affect AGB in different climatic forests (semi‐arid forests, semi‐humid forests and humid forests). Community‐level functional traits and stand structures together explained a great portion of the variance in AGB. The effect of community‐level functional traits was greater than that of stand structures in semi‐arid forests and semi‐humid forests, but smaller in humid forests. Further analyses showed that community‐level maximum tree height, stem density and tree size inequality were important explanatory variables. Although climate and species diversity had minor effects, the direct positive effect of mean annual precipitation (MAP) was still important, especially in semi‐arid forests. Synthesis . Community‐level functional traits but not species diversity were key drivers of AGB, indicating that tree species diversity loss may not impair AGB substantially in deciduous broadleaf forests in China. Moreover, stand structures also had strong effects on AGB in both semi‐arid forests and humid forests, highlighting the importance of structural complexity. In addition, MAP had a direct positive effect on AGB in semi‐arid forests and semi‐humid forests, and a future increase in drought might potentially reduce carbon storage in these forests. Abstract : Community‐level functional traits but not species diversity were key drivers of AGB, indicating that tree species diversity loss may not impair AGB substantially in deciduous broadleaf forests in China. Moreover, stand structures also had strong effects on AGB in both semi‐arid forests and humid forests, highlighting the importance of structural complexity. In addition, MAP had a direct positive effect on AGB in semi‐arid forests and semi‐humid forests, and a future increase in drought might potentially reduce carbon storage in these forests.